HEPATOTOXICIDADE DE NANOTUBOS DE CARBONO DE PAREDE MÚLTIPLA (NTCPM) NÃO FUNCIONALIZADOS EM CAMUNDONGOS - Almeida, Delita Vânia Bock (2012)
Carbon nanotubes are among the most promising nanomaterials with special features for use both as biomedical engineering. Several studies on the toxicity and feasibility are performed to assess its application in humans for delivery of drugs. In this study, we performed the evaluation of the hepatotoxic effect of carbon nanotubes multi-wall (MWCNT) by biochemical markers (albumin (ALB), total protein (TP), transaminases (ALT / AST), alkaline phosphatase (ALP), lactate dehydrogenase (LDH)) after administration via the intraperitoneal and intragastric in female mice at a dose of 1.5 mg / kg suspended in saline. Blood samples were analyzed one day, 7 and 30 days after treatment with MWCNT. The results after intraperitoneal administration showed a rise in serum total protein after 1 and 7 days. Serum albumin showed an increase in concentration after 7 days and 30 days after reduction. The activity of ALT levels increased only after 1 day, whereas the activity of AST showed an increase after 7 and 30 days. The LDH activity also increased significantly after 7 and 30 days. The FAL showed an increase in its activity after 1 and 7 days and a reduction after 30 days. The results obtained after intragastric administration of MWCNT showed an increase in serum total protein after 7 days and 30 days after reduction. Albumin did not show significant variations. The ALT activity increased significantly after 1 day and a reduction after 30 days. AST activity showed no significant differences in this way. The activity of LDH showed an increase after 7 days, no significant difference after 1 day and 30 days. The activity of ALP showed an increase after only one day. Serum albumin and total protein indicate an acute inflammatory process by both intraperitoneal and through activities of liver enzymes intragastric. As intraperitoneally showed severe liver injury while intragastrically showed mild reversible liver damage.